Relationships between experiences of humiliation on social networks, problematic phone use, and aggressive and altruistic behaviors in young adults - López-Mora, Clara; Carlo, Gustavo; López, Irene Huguet; González-Blázquez, Francisco Javier; Gasch, Elia Oliver (Frontiers in Psychology, 2024)
The purpose of this study was to analyze the relationships between cybervictimization in social networks, problematic smartphone use, aggressive behaviors, and prosocial altruistic tendencies in young adults. The sample consisted of 601 young adults (mean age = 19.96 years; SD = 2.27; 69.1% female) who were administered online assessments of experiences of humiliation on networks, problematic smartphone use, prosocial altruistic tendencies, and aggressiveness. Results indicated significant indirect effects of cyber victimization on aggressiveness and prosocial altruistic tendencies through problematic smartphone use. Problematic cell phone use explained the relationships between online humiliation and aggressive and prosocial altruistic behaviors. The results confirmed the positive relationship between cybervictimization and problematic cell phone use, consistent with previous research. However, the negative relationship between cybervictimization and altruistic prosocial tendencies was not corroborated. The findings emphasize the need to promote actions that foster social connectedness and interdependence among young individuals to develop their identity within the community.